Fabrication of porous Pt-doping heterojunctions by using bimetallic MOF template for photocatalytic hydrogen generation. (March 2017) - Lan, Meng; Guo, Rui-Mei; Dou, Yibo; Zhou, Jian; Zhou, Awu; Li, Jian-Rong
Abstract: Porous Pt-doping heterojunctions, Pt-ZnO-Co3 O4, Pt-ZnS-CoS, and Pt-Zn3 P2 -CoP were fabricated by firstly the oxidation, sulfurization, and phosphorization of ZnCo-zeolitic-imidazolate-framework (ZnCo-ZIF) and then the doping of Pt nanoparticles. They exhibit excellent photocatalytic activity towards hydrogen generation from water splitting. These bimetallic metal-organic-framework (MOF) derivatives maintain the porous framework skeleton of ZnCo-ZIF precursor, there by significantly enhancing the light utilization and simultaneously affording abundant exposed catalytic active sites. Most importantly, suitable band matching and strong electron coupling in these heterojunctions are achieved by using the bimetallic MOF template, which facilitate the efficient electron-hole separation and transportation. In addition, Pt nanoparticles distributed on the porous heterojunctions as electron traps can offer rich redox active sites for the hydrogen generation. Correspondingly, the hydrogen generation rate of Pt-ZnO-Co3 O4, Pt-ZnS-CoS, and Pt-Zn3 P2 -CoP was up to ~7.80, ~8.21, and ~9.15 mmol h −1  g −1, respectively, higher than those of respective ZIF-8 or ZIF-67-based derivatives. This work thus provides a new approach that using bimetallic MOF as template directs the fabrication of noble-metal doping heterojunctions to simultaneously enhance light absorption utilization, electro-hole separation, and transport, therefore promoting surface water oxidation reaction for efficient water splitting. Graphical abstract: A bimetallic MOF template approach is proposed to fabricate Pt-doping heterojunction photocatalysts for the hydrogen generation of water splitting. The obtained Pt-ZnO-Co3 O4, Pt-ZnS-CoS, and Pt-Zn3 P2 -CoP catalysts from the oxidation, sulfurization, and phosphorization of bimetallic ZnCo-zeolitic-imidazolate-framework (ZnCo-ZIF), respectively followed by Pt-doping exhibit excellent hydrogen generation performance. Highlights: A bimetallic MOF directed strategy is proposed for fabricating Pt-doping heterojunctions. Porous Pt-ZnO-Co3 O4, Pt-ZnS-CoS, and Pt-Zn3 P2 -CoP heterojunction photocatalysts are made. They exhibit excellent catalytic activity towards hydrogen generation from water splitting.